2003
DOI: 10.1155/s1023621x03000125
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Fluid Forces Induced by Rotor‐Stator Interaction in a Centrifugal Pump

Abstract: The pressure fluctuations and the radial fluid forces acting on the impeller, the pressures in the volute, as well as the vibration of the shaft in a centrifugal pump were measured simultaneously, and their relationship was investigated. Experiments were done for various diffuser vanes, flow rates, and rotating speeds. It was demonstrated that both the blade-pressure fluctuations and the volute static pressures are nonuniform circumferentially (not axisymmetrical) under off-design operating conditions and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 10 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Rotor-stator interaction [74,75] is the main factor of radial force, but The above analyses illustrate that the influence of tip clearance on pressure fluctuation has various forms in terms of magnitude, frequency, and variation trends for different types of pumps and turbines, and the variation of the impact is due to the complex flow pattern in those divers machineries.…”
Section: Radial Forcementioning
confidence: 99%
“…Rotor-stator interaction [74,75] is the main factor of radial force, but The above analyses illustrate that the influence of tip clearance on pressure fluctuation has various forms in terms of magnitude, frequency, and variation trends for different types of pumps and turbines, and the variation of the impact is due to the complex flow pattern in those divers machineries.…”
Section: Radial Forcementioning
confidence: 99%
“…Numerous studies investigated the characteristics of radial force theoretically, experimentally and numerically. Guo and Okamoto [18] simultaneously measured the radial fluid force acting on impellers, pressure fluctuations in volute and vibration of the shaft, and revealed their relationship under the rotor-stator interaction. Rodriguez et al [19] conducted theoretical analysis on frequency and amplitude of non-uniform fluid radial force for centrifugal pumps, and analyzed the relationship between dominant frequency and the number of blades and guide vanes, and the sequence of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure pulsation is known in literature as spreading in a form of waves in the whole hydraulic system [3]. Not only will the pump head, flow rate, and efficiency be influenced, but also potentially hydraulic exciting forces [4] and hydraulic components resonance will be induced [5] or even induce fatigue cracks of the construction [6,7]. Rzentkowski and Zbroja found that the pump acoustic behavior is exclusively governed by the pressure term, and the excitation frequency agrees well with the pressure pulsation frequency [8].…”
Section: Introductionmentioning
confidence: 99%